Rapid depletion of total sugars in stored sweet corn seeds limits shelf life - Ashoknarayanan, S; Umarani, R; Vanitha, C; Eevera, T; Djanaguiraman, M; Sudha, P; Anand, T (Plant Science Today, 2025)
Sweet corn, a naturally occurring mutant of field corn, is characterized by elevated levels of water-soluble polysaccharides due to the inhibition of sugar-to-starch conversion during seed development. This mutation results in seeds with lower carbohydrate reserves, which pose challenges such as reduced germination, seed vigour, poor field establishment, and limited shelf life. In this study, we investigated the relationship between food reserve levels and seed germination and vigour in sweet corn over a storage period. Seeds from both sweet and field corn, each with 8% moisture content, were stored under three conditions: ambient air, nitrogen, and vacuum. After six months, sweet corn seeds exhibited a 30% decrease in germination under ambient conditions, accompanied by a 73% reduction in total sugars. In contrast, field corn seeds showed a 6% decrease in germination and a 22% reduction in total starch under the same conditions. Notably, seed germination and seedling dry matter production were significantly and positively correlated with food reserve levels in both sweet and field corn across all storage environments. Total sugars were identified as a significant contributor to seed germination in sweet corn (p < 0.05), with regression models showing high R² values (0.9860 to 0.9998), indicating strong alignment with the observed data. These findings suggest that the depletion of total sugars in sweet corn seeds, driven by respiration and oxidation during storage, plays a critical role in the decline of seed quality and shelf life.